Analisis Materi Informasi Perikanan dan Kelautan Pada Program Siaran Pedesaan di RRI Pekanbaru - Ridar Hendri; Kusai Kusai (Berkala Perikanan Terubuk, 2016)
This research was conducted on December 2013 -January 2014 in RRI Pekanbaru. The research objective was to determine the characteristics of the material in the field of fisheries and marine on Rural Broadcasting Program, in Pekanbaru RRI,  consisting of: (1) the proportion of information; (2) types of information; (3) the duration of information package; and (4) the format of broadcast. This research used survey method. Data collected in this study is the script and documentetion recordings. Then, the data was analyzed descriptively (Hartono, J. H, 2004). The results showed, that RRI Pekanbaru only able to broadcast 156 (60%) of the 260 packages targeted Rural Broadcast Program, in 2013. Of that amount, package of fisheries and marine information, only 12 packages (7.70%). While the dominant broadcast package is a package of common development field (61.53%) and package agricultural sector (30.77%). Of the 12 packages of fishery and marine information presented, the majority (87%) contain material field of Aquaculture. The rest is matter Socioeconomic Fisheries field (13%). While the material four other fields (Fisheries Resource Utilization, Water Resource Management, Technology of Fishery and Marine Sciences), was never broadcast. Presentation of Rural Broadcast Program on RRI Pekanbaru, consists of 5 (five) segments. Namely Opener Bumper, Introduction to the Theme, Discussion of the Material, Interactive Dialogue, and the Bumper Cover. Material Description, is presented in the format of ‘Dialogue’ or ‘Drama’ (Fragment).